Analisis Penerapan Pencegahan Pencucian Uang dengan Metode Customer dan Enhanced Due Diligence di PT. Pegadaian Cabang Pancoran Mas - Rafka Muhammad Rizki; Lati Sari Dewi (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
Pegadaian as a non-bank financial institution has a strategic role in collecting funds and distributing financing through various financial services. This makes it a potential means for perpetrators of money laundering to disguise the proceeds of their crimes. Therefore, the government together with PT. Pegadaian implements a money laundering prevention policy, including the implementation of Customer Due Diligence (CDD) and Enhanced Due Diligence (EDD). This study aims to analyze the implementation of CDD and EDD carried out at PT. Pegadaian Pancoran Mas Branch. The research method applied is through a qualitative descriptive approach, using data collection techniques through documentation, interviews, and observations originating from three sources, including compliance officers and related parties who handle the Anti-Money Laundering and Prevention of Terrorism Financing (APU PPT) program.